2004
DOI: 10.1590/s0100-40422004000100014
|View full text |Cite
|
Sign up to set email alerts
|

Anestésicos locais: interação com membranas de eritrócitos de sangue humano, estudada por ressonância magnética nuclear de ¹H e 31P

Abstract: Recebido em 2/4/03; aceito em 7/8/03 LOCAL ANESTHETICS: INTERACTION WITH HUMAN ERYTHROCYTE MEMBRANES AS STUDIED BY 1 H AND 31 P NUCLEAR MAGNETIC RESONANCE. The literature carries many theories about the mechanism of action of local anesthetics (LA). We can highlight those focusing the direct effect of LA on the sodium channel protein and the ones that consider the interaction of anesthetic molecules with the lipid membrane phase. The interaction between local anesthetics and human erythrocyte membranes has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Considering the structure of lidocaine (Scheme ), the LD benzene group is most probably inside the apolar region of the micelle with the substituents protruding into the water shell. Previous studies using UV spectroscopy have indeed reported limited partitioning of LD inside the F127 micellar core, and FTIR studies have shown that uncharged local anesthetics are mainly located in the membrane/water interface, competing with the polar heads of phospholipids in binding with water molecules. , …”
Section: Resultsmentioning
confidence: 97%
“…Considering the structure of lidocaine (Scheme ), the LD benzene group is most probably inside the apolar region of the micelle with the substituents protruding into the water shell. Previous studies using UV spectroscopy have indeed reported limited partitioning of LD inside the F127 micellar core, and FTIR studies have shown that uncharged local anesthetics are mainly located in the membrane/water interface, competing with the polar heads of phospholipids in binding with water molecules. , …”
Section: Resultsmentioning
confidence: 97%